NONEQUIVALENCE IN THE ENGLISH-TO-INDONESIAN TRANSLATION OF BEHAVIORAL CLAUSES - Mujiyanto, Yan (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2011)
Translation has exposed a number of problems related to the linguistic domain. Suchproblems may stem from socio-cultural differences between the source language and thetarget language. They may also stem from the differences of the grammatical featuresbetween the two languages. Therefore, such problems have influenced the effort of achievingcorrespondence as well as equivalence; one of such problems is the existence of formalnonequivalence. This research aims to solve the problems of (1) how such formalnonequivalence appears in the translation of behavioral clauses and (2) how to achievefunctional equivalence through the presence of formal nonequivalence. This study wasdirected to deliberately analyze a written text in English and its translation in Indonesian. Itwas found out that formal nonequivalence may occur in word, phrase, and clause levels.Such formal nonequivalence has, however, facilitated the effort of achieveing functionalequivalence at clause level. In order to materialize functional equivalence at the clause level,the translation has been done by means of maintaining behavioral clauses or restructuringthem to form material clauses, mental clauses, or verbal clauses.